Structural, mechanical and thermal properties of bio-based hybrid composites from waste coir residues: Fibers and shell particles. (February 2016) - Essabir, H.; Bensalah, M.O.; Rodrigue, D.; Bouhfid, R.; Qaiss, A.
Highlights: Coir shells particles and fibers could significantly increase the properties of PP. The interface fillers–matrix has been improved by the using a coupling agent. Hybridization has a positive effect to promote composites with improved properties. Coir shells and fibers have a potential as bio-filler into polymeric matrix. Abstract: Polypropylene hybrid composites were produced by using coir fibers and coir shell particles at a total weight content of 20%. The effect of hybridization and coupling agent on the morphological, structural, thermal and mechanical properties was investigated. The morphological and structural results show that the coupling agent increased filler/matrix interfacial adhesion. Thermogravimetric analysis indicates that thermal degradation of shell particles (285/465 °C) is lower than coir fibers (331/474 °C). The combination of coir fibers and particles has a positive effect on the Young's modulus with hybrid composites showing intermediate values between non-hybrid composites (improvement between 35 and 50%). The modeling of the mechanical behavior of the manufactured composites was done by physical models (Voigt, Reuss, and Tsai–Pagano models). Graphical abstract: